Total knee arthroplasty using hinge joints: Indications and results - Rodríguez-Merchán, E. Carlos (EFORT Open Rev, 2019)
Possible indications for a rotating hinge or pure hinge implant in primary total knee arthroplasty (TKA) include collateral ligament insufficiency, severe varus or valgus deformity (> 20°) with relevant soft-tissue release, relevant bone loss, including insertions of collateral ligaments, gross flexion-extension gap imbalance, ankylosis and hyperlaxity. The use of hinged implants in primary TKA should be limited to the aforementioned selected indications, especially for elderly patients. Potential indications for a rotating hinge or pure hinge implant in revision TKA include infection, aseptic loosening, instability and bone loss. Rotating hinge knee implants have a 10-year survivorship in the range of 51% to 92.5%. Complication rates of rotating hinge knee implants are in the range of 9.2% to 63%, with infection and aseptic loosening as the most common complications. Although the results reported in the literature are inconsistent, clinical results generally depend on the implant design, appropriate technical use and adequate indications. Considering that the revision of implants with long cemented stems can be challenging, in the future it would be better to use shorter stems in modular versions of hinged knee implants. Cite this article: EFORT Open Rev 2019;4:121-132. DOI: 10.1302/2058-5241.4.180056